You have new items in your feed. Click to view.
Q: Find the difference: 48 – (–23)
A: 48 – (–23) = 48 + 23 = 71
Question
Updated 11/29/2014 4:33:30 AM
Edited by andrewpallarca [11/29/2014 4:33:29 AM], Confirmed by andrewpallarca [11/29/2014 4:33:30 AM]
Rating

Questions asked by the same visitor
an “educated guess” a.) a definition b.) a negation c.) a conjecture d.) a counterexample
Weegy: what is the question? User: a false example is? a.) a hypothesis b.) a conjecture c.) a theorem d.) a counterexample Weegy: conjecture User: make a conjecture based on the given information: “Allen studied for his geometry test. There are 20 questions on the test and he has answered the first 14 correctly.” (More)
Question
Updated 3/3/2014 11:38:35 AM
an educated guess is c.) a conjecture. a false example is d.) a counterexample.
An educated guess is a conjecture.
Confirmed by andrewpallarca [3/3/2014 11:37:39 AM]
A false example is a counterexample.
solve: 12(–5)(8) = n
Weegy: The result of 12(–5)(8) = n is -480 = n. User: Find the quotient: -85/-17 (More)
Question
Updated 8/26/2014 12:23:47 PM
-85/-17 = 5
Confirmed by jeifunk [8/26/2014 12:23:29 PM]
Simplify: (m+6n-14p) - (6m-3n+11p)
Question
Updated 10/26/2014 5:19:15 PM
(m+6n-14p) - (6m-3n+11p)

= m + 6n - 14p - 6m + 3n - 11p;

= -5m + 9n - 25p
Confirmed by jeifunk [10/26/2014 5:23:02 PM]
Solve for y: y/3+9=9
Weegy: do you have any questions? :) User: Solve for “y”: y/3+9=9 Weegy: do you have any questions? :) (More)
Question
Updated 7/13/2014 1:07:59 PM
y=0
y/3 + 9 = 9;

y/3 = 9 - 9;

y/3 = 0;

y = 0 * 3;

y = 0
y/3+9=9
Question
Updated 3/28/2015 9:48:23 AM
y/3 + 9 = 9

y/3 = 9 - 9;

y/3 = 0;

y = 0 * 3;

y = 0
Confirmed by yumdrea [3/29/2015 11:16:09 PM]
*
Get answers from Weegy and a team of really smart lives experts.
Popular Conversations
What's 3 * 4
Weegy: Synonyms for the word "say" which are bigger in length and in impact, are communicate, ...
Solve for x 3x + 3 - x + (-7) > 6 A. x > 2.5 B. x > ...
Weegy: (3x + 1) + 8 = 4(x + 9), 3x + 9 = 4x + 36, 3x - 4x = 36 - 9, -x = 27, x = -27 User: Solve this ...
When adding a suffix that begins with a consonant, the general rule ...
Weegy: If the ending begins with a consonant, the spelling of the root word is usually not altered.
S
L
Points 265 [Total 283] Ratings 0 Comments 195 Invitations 7 Offline
S
L
R
Points 145 [Total 296] Ratings 1 Comments 5 Invitations 13 Offline
S
L
Points 135 [Total 135] Ratings 0 Comments 135 Invitations 0 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.